The Influence of Some Types of Biological Agent Formula and the Different Application Time on the Population of the Biological Agent Bacteria and The Chili Plants - Yenny Wuryandari; Sri Wiyatiningsih Suwandi (Nusantara Science and Technology Proceedings)
One alternative for suppressing disease and promoting plant growth is to use the formula for biological agents. The research aims to determine the best formulation of Pseudomonad fluorescent Pf-122 and to determine the right application time in stimulating the growth of chili plants. The formula is made by mixing bacterial active ingredients with semi-natural media of rice crab by hydrolyzing using pineapple and papaya, as well as organic fertilizer. The study used 2 treatment factors. The first factor is the type of formula consisting of control using only Pf-122 (F0), Pf-122 + K (rice crab) (F1), Pf-122 + KN (rice crab by hydrolyzing using pineapple) (F2), Pf-122 + KP (rice crab by hydrolyzing using papaya) (F3). The second factor is application time; watering five days before planting and watering while planting. The results showed that plant growth, namely plant height, number of leaves, root length, and root weight did not differ statistically significantly from all treatment types of application. When viewed from the time of application of the formula, there is also no difference in the growth of chili plants. However, when viewed from the average value, the control without formula tends to show a lower growth value compared to that given the formula. In the generative growth phase, which is when the flowers appear, the chili plants are given a formula faster than without the formula. Application for all types of formulas, the time of occurrence of flowers is not significantly different. The number of Pf-122 populations in the rhizosphere decreases and increases are unstable in all formula applications. The high Pf-122 population in the rhizosphere does not show high chili growth either